On the Practical Robustness of the Nesterov’s Accelerated Quasi-Newton Method - Indrapriyadarsini, S.; Ninomiya, Hiroshi; Kamio, Takeshi; Asai, Hideki (Proceedings of the AAAI Conference on Artificial Intelligence, 2022)
This study focuses on the Nesterov's accelerated quasi-Newton (NAQ) method in the context of deep neural networks (DNN) and its applications. The thesis objective is to confirm the robustness and efficiency of Nesterov's acceleration to quasi-Netwon (QN) methods by developing practical algorithms for different fields of optimization problems.